ChemInform Abstract: Binaphthyl Based Molecules for Asymmetric Organocatalytic Aldol Reactions: Recent Developments from a Successful Record. Issue 3 (January 2015) - Almeida, Ana R.; Neves, Angela C. B.; Abreu, Artur R.; Calvete, Mario J. F.; Pereira, Mariette M.
Abstract Review: 82 refs.